Agonistic Behaviour and Sound Production during Male–Male Varunid Crabs (Cyrtograpsus angulatus, Dana 1851) Encounters - Ceraulo, Maria (2022)
Crustacean sounds are the main contributor to shallow water soundscape biophonic components. Here, we investigate the sound production of Cyrtograpsus angulatus, one of the most important intertidal decapods of the Southwestern Atlantic Ocean. Underwater audio and video were recorded during encounters among male pairs. Two kinds of experimental settings were conducted involving same size (SS) and different-size (DS) male crabs. Behavioural states, behavioural events and sound emission were investigated. SS spent more time in contact and still behaviour and showing competitive interactions than did DS. Crabs presented body displays involving chelae, legs, and maxillae movements with the same frequency in both settings. Our results demonstrate the production of impulsive sounds in male C. angulatus with high rates during contact and still behaviour (specifically during agonistic interactions and body displays without contact between individuals). Furthermore, we were able to describe behaviour-related variability within impulsive sounds. These outcomes provide a better understanding of the role and behavioural context of these sounds in the natural soundscape.